Kualitas Pelayanan Pajak Kendaraan Bermotor dan Bea Balik Nama Kendaraan di Kantor Samsat Kota Palangka Raya Provinsi Kalimantan Tengah - Shanty Bahar Ising; Novi Damayanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This research aims to know, describe and analyze the quality of the motor vehicle tax and the customs name (PKB and BBNKB) in the office of SAMSAT City Palangka Raya Province of central Kalimantan. The method used is qualitative exploitation, research conducted is a descriptive study where SAMSAT (one-stop Manunggala administration system) Palangka Raya City was chosen as the location of research. Data Collection Techniques use interviews, documentation, and observations. Based on the research results that the quality of the vehicle tax Service and the name of the motor vehicle (PKB and BBNKB) in the city Palangka Raya Province of central Kalimantan. Regarding the timeliness of the waiting time is good, officers work in accordance with the prescribed clock and related process waiting time depends on readiness of the applicant's requirements, but based on a research interview with the community that for the processing time is still Poorly can be in the value of a fast service that is not through the specified stages.